PENDAMPINGAN UMKM DALAM PENGURUSAN LEGALITAS USAHA MELALUI SERTIFIKASI HALAL DAN NIB PADA KOMUNITAS UMKM DESA SUKOANYAR - Ahsin, Nurul; Fauzi, Achmad Rizki; Cahyani, Aisyah; Faizah, Aulia Laily; Sunnah, Kharisma Danis; Husna, Tsalsabila Nikmatul; Sari, Wulan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This mentoring program discusses strategies for optimizing halal certification and obtaining a NIB (Business Identification Number) for MSMEs, aiming to improve business legality and consumer trust by meeting officially recognized halal standards. The mentoring program was conducted in Sukoanyar Village, Mojo District, Kediri Regency, East Java, using the Participatory Action Research (PAR) method. The mentoring program offers strategies and practical steps that MSMEs can take to streamline their halal certification process. Furthermore, the mentoring program also features speakers from the Halal Center who will share their experiences and innovative solutions to facilitate MSMEs in obtaining halal certification.